Syntheses, structures, and magnetic properties of homodinuclear lanthanide complexes based on dinucleating Schiff base ligands. Issue 46 (5th November 2015) - Gao, Feng; Yang, Feng-Lei; Zhu, Guang-Zhou; Zhao, Yue
Abstract : Two series of homodinuclear lanthanide(iii ) complexes were synthesized and characterized. Magnetic studies reveal the weakly antiferromagnetic coupling between paramagnetic Ln ions and enhanced relaxation of magnetization for Dy2 complexes. Abstract : The first two families of homodinuclear lanthanide(iii ) complexes, formulated as [(LOEt )2 Ln2 (L1)] and [(LOEt )2 Ln2 (L2)] (Ln 3+ = Dy 3+, Tb 3+, Ho 3+, Gd 3+, and Y 3+ ; L1 4− = 2, 2′, 2′′, 2′′′-[1, 2, 4, 5-benzenetetrayltetrakis(nitrilomethylidyne)]tetrakisphenolate; L2 4− = 2, 2′, 2′′, 2′′′-[[1, 1′-biphenyl]-3, 3′, 4, 4′-tetrayltetrakis(nitrilomethylidyne)]tetrakis(4-chlorophenolate); LOEt − = (η 5 -cyclopentadienyl)tris(diethylphosphito- p )cobaltate(iii )), were successfully synthesized based on Kläui's tripodal building block NaLOEt and two dinucleating Schiff base ligands, H4 L1 andH4 L2, respectively. Single-crystal X-ray analyses show that these lanthanide complexes have two seven-coordinated metal binding sites, linked to each other with a phenyl or biphenyl bridge. Variable temperature dc magnetic measurements reveal the weakly antiferromagnetic coupling between paramagnetic lanthanide ions, while ac magnetic data exhibit the field-induced relaxation of magnetization for the corresponding Dy2 complexes1 and6 . A further magnetic dilution study for1 suggests that the slow magnetic relaxation originates from the single-ion magnetic behaviour of Dy 3+ ions.